Microbial spatial footprint as a driver of soil carbon stabilization - A. N. Kravchenko (Nature Portfolio, 2019)
The processes driving soil carbon accretion remain to be poorly understood. Here the authors combined X-ray micro-tomography and zymography to demonstrate that plant-stimulated soil pore formation is a major, hitherto unrecognized, determinant of whether new C inputs are stored or lost to the atmosphere.